Variations in Dilution of DSSE 10 Antibody in Immunocytochemistry Technique to Detect Dengue-3 Virus in Aedes aegypti Mosquitoes - Dyah Widiastuti; Sitti Rahmah Umniyati (Pusat Kedokteran Tropis, 2011)
Introduction: Dengue viruses, globally the most prevalent arboviruses, are transmitted to humans by persistently infected Aedes mosquitoes. The most important vector of Dengue virus is the mosquito Ae. aegypti, which should be the main target of surveillance and control activities. Virologic surveillance for Dengue viruses in its vector has been used as an early warning system to predict outbreaks. Detection of Dengue virus antigen in mosquito head squash using immunocytochemical streptavidin biotin peroxidase complex (SBPC) assay is an alternative method for Dengue vector surveillance.Objectives: The study was aimed to compare several variations of MAb DDSE10 dilutions used in immunocytochemical SBPC assay to detect Dengue virus infection in head squash of Ae. aegypti.Methods: The study design was experimental. Artifi cially-infected adult Ae. aegypti mosquitoes of DENV 3 were used as infectious samples and uninfected adult Ae. aegypti mosquitoes were used as normal ones. The immunocytochemical SBPC assay using monoclonal antibody DSSE10 with 4 variations of dilution (1:5, 1:10, 1:20, and 1:50) was applied on mosquito head squash to detect Dengue virus antigen. The results were analyzed descriptively.Results: All variants of MAb DSSE10 dilutions in immunocytochemical SBPC assay showed positive imunoreaction in infected mosquito head squash. All variants of MAb DSSE10 dilutions in immunocytochemicalSBPC assay showed negative immunoreaction in uninfected mosquito head squash.Conclusion: Monoclonal antibody DSSE10 could be used in immunochemistry technique to detect Dengue-3 virus antigen in Aedes aegypti infected intrathoracally, with 1:50 dilution.Keywords: Aedes aegypti, Dengue virus, Immunocytochemical, SPBC, Monoclonal Antibody DSSE-10